Nests and Eggs of Familiar British Birds, Second Series : Described and Illustrated; with an Account of the Haunts and Habits of the Feathered Architects, and their Times and Modes of Building - Adams, H. G. (Henry Gardiner), 1812?-1881 (Salt Lake City, UT : Project Gutenberg, 2012)
"Nests and Eggs of Familiar British Birds, Second Series" by H. G. Adams is a scientific publication written in the mid-19th century. The work provides detailed descriptions and illustrations of the nests and eggs of various British bird species, along with insights into their habitats and building habits. It aims to educate readers on the biology and ecology of these birds. The beginning of this work introduces readers to the concept of an egg, discussing its definition and significance in the animal kingdom. The author encourages both young and old to contemplate the nature of eggs and their role in life cycles, emphasizing the intricate processes involved in the development of embryos within eggs. Moreover, the text piques curiosity by alluding to the wonders of natural history and the different forms eggs take among various species, preparing the reader for a profound exploration of avian life. (This is an automatically generated summary.)
Release date is 2012-12-04
E-text prepared by Chris Curnow and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (http://archive.org)
Keywords: Birds -- Nests; Birds -- Great Britain; Birds -- Eggs